2021
DOI: 10.21467/jmm.8.1.52-66
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Physical and Comfort Properties of Yarns and Hand-woven Fabrics Produced from Virgin and Recycled Fibers

Abstract: Products produced from textile industries cannot meet the needs for human kind since the population of the world grows exponentially; due to this the recycling of textile materials has gained massive importance in textile and clothing sector. In this study, it was aimed to analyse recycled fibers effect on the yarn and hand loom fabrics as their proportion increases. For this purpose, OE rotor yarns produced by varying the recycled fibers proportion at 25%, 50, and 75% and compared with 100% virgin cotton yarn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…ÜTEBAY et al [10] investigated the effects of cotton textile waste properties on recycled fiber quality and they showed that the recycled fibre quality and the resultant yarn properties are associated with the waste fabric properties and shredding parameters. AWGICHEW et al [11] analysed the recycled fibers effect on the yarn and woven fabrics as their proportion increases, and their results showed that the yarns and fabrics produced from recycled fibers blended with virgin cotton are suitable for applications where the strength of yarns and fabric are less critical. MEMON et al [12] examined the properties of the yarns produced from recycled cotton fiber blends for proportion optimization and to check whether they can be used for denim fabric production.…”
Section: Introductionmentioning
confidence: 99%
“…ÜTEBAY et al [10] investigated the effects of cotton textile waste properties on recycled fiber quality and they showed that the recycled fibre quality and the resultant yarn properties are associated with the waste fabric properties and shredding parameters. AWGICHEW et al [11] analysed the recycled fibers effect on the yarn and woven fabrics as their proportion increases, and their results showed that the yarns and fabrics produced from recycled fibers blended with virgin cotton are suitable for applications where the strength of yarns and fabric are less critical. MEMON et al [12] examined the properties of the yarns produced from recycled cotton fiber blends for proportion optimization and to check whether they can be used for denim fabric production.…”
Section: Introductionmentioning
confidence: 99%